Profissionais desviantes no condado : um estudo sobre carreiras - Silva, Sebastião Victor Oliveira Acioli da (2015)
This thesis aims, broadest, analyze the career of women who exercise prostitute craft in private establishments in the Shire. The empirical universe therefore consists the adult female prostitution exercised in enclosed spaces and not in open environments such as the street. More specifically, it was taken as central to understanding how someone becomes a prostitute, that is, what are the steps, the routes and the contingencies that contribute to lead someone to exercise this office, and often seek success in career? To cope with this issue, this work is between the sociology of professional groups and the sociology of deviance, once it is the socialization in an occupation highly stigmatized and deviant and that involves in the process informality as a backdrop.